Lady knight [compact disc, unabridged] - Pierce, Tamora (Pierce, Tamora. Protector of the small, 2009)
When she became a knight, eighteen-year-old Kel hoped to be given a combat post, but instead she finds herself named commander of an outpost of refugees, where she must face the unnatural forces of the evil Balyce.